A survey of patients' attitudes to upper gastrointestinal endoscopy identifies the value of endoscopist–patient interactive factors. Issue 4 (4th May 2011) - Hydes, T; Yusuf, A; Pearl, DS; Trebble, TM
Abstract : Objective: To determine patients' self-reported preferences and expectations for outpatient upper gastrointestinal (UGI) endoscopy, including patients' priorities in obtaining a satisfactory healthcare experience, preprocedure anxiety and its causes, and preferred staff roles. Design: A composite, dedicated endoscopy questionnaire was used. This included demographic information, validated Likert scale anxiety-related questions and a 15-point ranking scale of aspects of care (1=most important to satisfaction; 15=least important). Setting and patients: Unselected patients attending for an elective UGI endoscopy at two separate units were surveyed on randomly identified days. Results: A total of 202 out of 254 patients agreed to participate (79.5%). The values identified as most important to patients included technical skill (2.8) and personal manner of the endoscopist (4.9) and the nurses and support staff (5.8), control of discomfort (5.6) and adequacy of the preprocedure explanation (5.8). The factors considered least important included noise levels (12.5), privacy (10.7) and cleanliness (8.7). Moderate to severe anxiety was recorded in half of the patient cohort, predominantly due to anticipation of pain or the results of the procedure. Most patients preferred the endoscopist to discuss the findings of the endoscopy but expressed no preferences regarding the preprocedure explanation. Conclusion: Patients undergoing UGI endoscopy appear to highly prioritise aspects of care relating to interaction with the endoscopist and the procedure itself. Environmental factors are considered to have much less value. These findings may assist in service redesign around patient-centred care and the development of patient satisfaction surveys in endoscopy.